KEPEMIMPINAN DEKOMKRATIS SEBAGAI UPAYA PENANAMAN PENDIDIKAN ANTI KORUPSI - Indriawati (STAI Pelabuhan Ratu, 2025)
This study aims to examine the democratic leadership style as a strategic approach to instilling anti-corruption education values. Leadership is considered to have a significant influence in shaping organizational culture and individual behavior, particularly in the field of education. Anti-corruption education is one of the key instruments in the effort to eradicate corruption from an early age, and its success is largely determined by the example set by leaders. This research employs a qualitative-descriptive method based on library research. The findings show that: (1) Democratic leadership promotes active participation, collaboration, and shared decision-making, all of which support the cultivation of integrity values; (2) Anti-corruption education is effectively implemented through open and communicative leadership patterns; and (3) Building an anti-corruption culture requires role models of integrity from leaders and an educational system that consistently instills anti-corruption values on an ongoing basis.